A biochemical approach for identifying plastics exposure in live wildlife. Issue 1 (17th October 2014) - Hardesty, Britta D.; Holdsworth, Daniel; Revill, Andrew T.; Wilcox, Chris; Davey, Matthew
Summary Plastic pollution is a long‐standing ubiquitous issue. Global use of plastics is continuing to rise, and there is increasing interest in understanding the prevalence and risk associated with exposure of wildlife to plastics, particularly in the marine environment. In order To facilitate an assessment of ingestion of plastics in seabird populations, we developed a minimally invasive tool that allows for detection of exposure to plastics. Using a simple swabbing technique in which the waxy preen oil is expressed from the uropygial gland of birds, we successfully tested for the presence of three common plasticizers: dimethyl, dibutyl and diethylhexyl phthalate [dimethyl phthalate, dibutyl phthalate and bis(2‐ethylhexyl)‐phthalate, respectively]. These plasticizers are prevalent in the manufacturing of plastic end‐user items which often end up in the marine environment. Using gas chromatography–mass spectrometry and protocols to reduce background contamination, we were confidently able to detect targeted plasticizers at low levels. The method described has broad applicability for detecting plastics exposure in wildlife at individual, population and species levels. Furthermore, the approach can be readily modified as needed to survey for plastics exposure in taxa other than seabirds. Applying the simple, minimally invasive approach we describe here is particularly appealing for detecting plastics exposure at population and species levels, it shows promise for quantification and it has no observed detrimental impacts to wildlife.